The Relationships between Perception Values, Trust, and Engagement in Audio-Based Social Platforms - Eurjirapongpun, Budsara; Penkitti , Apipol; Lekmat, Laddawan (Modern Management Frontier Journal, 2024)
Audio-based social platforms (ABSPs) which are the audio chat online social network, e.g., Clubhouse; Twitter space; and Facebook live) has become well-known rapidly across the world. This study aims to examine the relationships between the perceived values, consumer’s trust, and engagement. The questionnaire was used to collect data from a sample of 388 ABSPs users, especially with age of 25-to-34-years-old. The results showed that the hedonic and social values were directly related to user engagement, while the utilitarian value was indirectly related to user engagement through user's trust in speakers. Besides, the hedonic value was positively related to user's trust in platforms.